Uji Efektivitas Antidiabetik Kombinasi Ekstrak Daun Senggani (Melastomapolyanthum .Bl) dan Glibenklamid dalam Menurunkan Kadar Glukosa Darah pada Mencit (Mus Musculus): Antidiabetic Effectiveness Test of A Combination of Senggani (Melastoma Polyanthum .Bl) and Glibenclamide Leaf Extract in Reducing Blood Glucose Levels in Mice (Mus Musculus) - Sry Widyastuti; Samsidar Usman; Dina Rahayu (Jurnal Sains dan Kesehatan, 2022)
This study aims to determine the antidiabetic effectiveness of the combination of Senggani leaf extract (Malestoma polyanthum Bl.) And Glibenclamide against alloxan-induced mice. This study used 15 male mice divided into 5 groups and each group consisted of 3 male mice, group I was given Na.CMC 1% w / v, groups III, IV, V were each given a combination of senggani leaf extract 90 mg / kg, 180 mg / kg, 360 mg / kg and 5 mg of glibeclamide as the treatment group, and for group II were given glibenclamide suspension 5 mg for comparison. Alloxan 150 mg / KgBW was used as an inducer of diabetes. Measurement of blood glucose levels was carried out three times, namely initial glucose measurement, post-induction glucose measurement and post-treatment glucose measurement. The results showed that giving senggani leaf extract with a concentration of 90 mg / kg BW, 180 mg / kg BW, 360 mg / kg BW had an antidiabetic effect in male mice. Senggani leaf extract 360 mg / kg BW showed the most effective antidiabetic effect, but still more smaller than the 5 mg glibenclamide suspension.